Evaluating Secondary School Students' Conception of Force and Motion Using a Four-Tier Diagnostic Test - Saputra, Winata Tegar; Rusyati, Lilit (Journal of Science Education Research, 2025)
A major problem in education is misconceptions. The Four-Tier Diagnostic Test is one way to identify misconceptions. Since no research uses the Four-Tier Diagnostic Test to assess force and motion, the particular study aimed to investigate students’ conceptions of force and motion topics by using a four-tier diagnostic test with secondary school students and to identify the concept of force and motion topics about which most students hold misconceptions. The instrument was developed through several steps, including a preliminary study, content validity with three experts, construct validity, and reliability, resulting in 17 questions from an initial 28 questions. This research evaluated 174 students using a cross-sectional survey design and convenience sampling. The research shows that the students’ conceptions are 27.92% Scientific Knowledge, 27.92% False Positive, 6.76% False Negative, 18.59% Misconceptions, and 23.9% Lack of Knowledge. Most students have misconceptions about displacement, Newton’s law, and vectors. Also, this research included a semi-structured interview with a teacher who revealed some reasons the students demonstrate these categories of conceptions. The findings implied that the scientific knowledge conceptions of students are important, especially in physics, and teachers find the effective teaching strategy for students to increase their scientific knowledge.